Health inequalities in children and adolescents: a scoping review of the mediating and moderating effects of family characteristics - Blume, Miriam; Rattay, Petra; Hoffmann, Stephanie; Spallek, Jacob; Sander, Lydia; Herr, Raphael; Richter, Matthias; Moor, Irene; Dragano, Nico; Pischke, Claudia Ruth; Iashchenko, Iryna; Santos-Hövener, Claudia; et al. (International journal of environmental research and public health, 2021)
This scoping review systematically mapped evidence of the mediating and moderating effects of family characteristics on health inequalities in school-aged children and adolescents (6-18 years) in countries with developed economies in Europe and North America. We conducted a systematic scoping review following the PRISMA extension for Scoping Reviews recommendations. We searched the PubMed, PsycINFO and Scopus databases. Two reviewers independently screened titles, abstracts and full texts. Evidence was synthesized narratively. Of the 12,403 records initially identified, 50 articles were included in the synthesis. The included studies were conducted in the United States (n = 27), Europe (n = 18), Canada (n = 3), or in multiple countries combined (n = 2). We found that mental health was the most frequently assessed health outcome. The included studies reported that different family characteristics mediated or moderated health inequalities. Parental mental health, parenting practices, and parent-child-relationships were most frequently examined, and were found to be important mediating or moderating factors. In addition, family conflict and distress were relevant family characteristics. Future research should integrate additional health outcomes besides mental health, and attempt to integrate the complexity of families. The family characteristics identified in this review represent potential starting points for reducing health inequalities in childhood and adolescence.
Published: 21 July 2021
Gesehen am 16.12.2022